Acessibilidade Web para deficientes visuais: uma análise de repositórios institucionais de universidades federais do Nordeste do Brasil - Aline Karoline da Silva Araújo (2022)
The Open Access Movement promotes full accessibility to scholarly and scientific literature, without restrictions to access or use. Free access to scientific information means removing all barriers that may hinder access to its contents. Open access institutional repositories, which are informational environments originated from that movement, follow its philosophy of promoting democratic access to all users, regardless of them having any kind of physical, sensorial or cognitive impairment. In that context, it is important to investigate whether those repositories are properly built to foster free access to scientific knowledge. This dissertation aims to analyze the accessibility of web pages provided by institutional repositories in the Northeast of Brazil with respect to visually impaired users, by checking their compliance to the WCAG 2.1 accessibility guidelines. To that end, we selected a sample of eight institutional repositories belonging to higher education institutions located in the Northeast of Brazil. Data collection was performed by applying the AccessMonitor tool to two types of Web pages - the initial page, and the page containing metadata of a specific document - of each of the institutional repositories observed. AccessMonitor is an automatic validator tool developed by the Foundation for Science and Technology of Portugal, whose goal is to assess the application of accessibility guidelines in Web pages in internet sites. To that end, the tool refers to version 2.1 of the Web Content Accessibility Guidelines (WCAG) issued by the World Wide Web Consortium (W3C). The results of this research show that none of the eight institutional repositories that we analyzed satisfy the minimum requirements of compliance level "A" established in WCAG 2.1. We also point out that the quantitative indices of the institutional repositories varied between 7.3 and 4.5 (main page), with a mean value of 6.05, and between 5.7 and 4.2 (page of a specific document), with a mean value of 4.99. The results obtained through the analysis of the reports provided by AccessMonitor identified 26 errors and warnings, divided into three compliance levels: 18 in level "A", 3 in level "AA" and 5 in level "AAA". We analyzed these problems separately, and we recommend corrections based on the instructions of WCAG 2.1 and AccessMonitor itself to improve the web accessibility of the institutional repositories sampled by this research. Keywords: Web Accessibility, Open Access Movement, Institutional Repositories, Visual Impairment.